Sensitive fluorescence-based detection of magnetic field effects in photoreactions of flavins. - Evans, E; Li, J; Storey, J; Maeda, K; Henbest, K; Dodson, C; Hore, P; Mackenzie, S; Timmel, C (2015)
Magnetic field effect studies have been conducted on a variety of flavin-based radical pair systems chosen to model the magnetosensitivity of the photoinduced radical pairs found in cryptochrome flavoproteins. Cryptochromes are blue-light photoreceptor proteins which are thought to mediate avian magnetoreception, an hypothesis supported by recent in vitro observations of magnetic field-dependent reaction kinetics for a light-induced radical pair in a cryptochrome from the plant Arabidopsis thaliana. Many cryptochromes are difficult to express in large quantities or high concentrations and are easily photodegraded. Magnetic field effects are typically measured by spectroscopic detection of the transient radical (pair) concentrations. Due to its low sensitivity, single-pass transient absorption spectroscopy can be of limited use in such experiments and much recent work has involved development of other methodologies offering improved sensitivity. Here we explore the use of flavin fluorescence as the magnetosensitive probe and demonstrate the exceptional sensitivity of this technique which allows the detection of magnetic field effects in flavin samples at sub-nanomolar concentrations and in cryptochromes.